Poder local e capital político-familiar: estratégias de poder, familismo e clientelismo da família Leite no sertão paraibano – Desterro - PB (1977- 1989). - Silva, Dêis Maria Lima Cunha (2020)
This text aims to analyze the political performance of the Leite family in the sertão of Paraíba, in the city of Desterro-PB, to verify their influence on local politics and their clientele and family network on local politics between the years of 1977 to 1989. Our study is inserted in the time frame of the “slow, gradual and safe” transition of the Brazilian Military Regime. Our intention was to analyze the political and family arrangements articulated by the Leite family group to rise to elective and public positions, to remain ahead of the municipal executive and legislative power for approximately three decades of the twentieth century in the city of Desterro-PB, covering six uninterrupted terms. We sought the political practices of clientelism and familism as a practice of power and construction of the network of influence of the Leite family in the city of Desterro-PB. To subsidize the research, we consulted documentary sources such as printed newspapers of state circulation - The newspaper A União and the newspaper O Norte. We used letters and telegrams available in the archives of the city hall of Desterro-PB, Minutes of the City Council and we made use of oral research through interviews. From a theoretical and methodological point of view, we adopted the perspective of analysis of the socalled New Political History, which opens up a range for different historical sources and enables us to research the political field in order to perceive political practices without being attached to the deeds, to the exclusivity of the actions of a single political subject (REMOND, 1996); (BERSTEIN, 1998); (MOTA, 2009), but also the articulations to conquer and stay ahead of the government (MONTEIRO, 2016). This study is inserted in the line of Research: History and Regionalities of the PPGH/UFPB, because it dialogues with the emphasis on regional historicity and excels in this space of performance through the analysis of the role of the agents involved and the processes related to the spaces national and global ones.